(untitled) (BioLaw Journal - Rivista di BioDiritto, 2022)
The contribution, starting from the well-known problem of the “new rights”, highlights the further difficulties that this general theme encounters when it is framed in the particular context of criminal execution. Focusing attention on issues related to affectivity and sexuality, the author highlights the critical issues related to their recognition and protection. She maintains that these critical issues must be traced back to a devaluing reading of the sexual dimension in emotional relationships and to persistent distorted conceptions of the function of punishment.